The association between parent-child relationship and problematic internet use among English- and Chinese-language studies: A meta-analysis - Zhu, Yalin; Deng, Linyuan; Wan, Kun (Frontiers in Psychology, 2022)
As past studies of the association between parent-child relationship and problematic internet use show mixed results and are influenced by many factors, this meta-analysis of 75 primary Chinese and English language studies from 1990 to 2021 with 110,601 participants (aged 6−25 years) explored (a) the overall association between parent-child relationship and problematic internet use, and (b) whether the association is affected by their types, country, measures, objects of the parent-child relationship, gender, age, year and publication types. We used funnel plots, Classic fail-safe N and Egger's test to test for publication bias and for moderation with the homogeneity tests. The results showed a negative association between quality of parent-child relationship and problematic internet use (r = −0.18, 95% CI = [−0.20, −0.15]). The moderation analysis found that compared with internet addiction tendency, the association between social media addiction and parent-child relationship was stronger. Moreover, the association between the parent-child relationship and problematic internet use of emerging adults (18–25 years old) was stronger than that of adolescents (12−18 years old). Furthermore, the negative association between parent-child relationship and problematic internet use was weaker (a) in Italy than those in Turkey and China, (b) when using CPS (Closeness to Parents Scale), IPPA (Inventory of Parent and Peer Attachment), or PARQ (Parent-Child Relationship Questionnaire) measuring parent-child relationship than using PCCS (Parent-Child Communication Scale), (c) when using IAT measuring problematic internet use rather than using IGDS or APIUS. Hence, these results indicate a negative association between parent-child relationships and problematic internet use, and the association is moderated by types of problematic internet use, age, country, scales of both parent-child relationship and problematic internet use.